Differences in benthic macroinvertebrate structure of headwater streams with extreme hydrochemistry - Horecký, Jakub; Rucki, Jan; Krám, Pavel; Křeček, Josef; Bitušík, Peter; Špaček, Jan; Stuchlík, Evžen (Biológia, 2013)
A synoptic study of acidified mountain streams covering six Czech sites was performed. The aim was to provide biological data from small mountain streams in catchments with historically high acid atmospheric deposition, which have so far been subject of intensive long-term monitoring of hydrology and hydrochemistry only, in order to follow the development of the structure of benthic macroinvertebrates in the course of recovery from acidification. We focused on small headwater streams with minimum human influence in the catchment and relatively low concentrations of dissolved organic matter. The sites were classified according to their water pH status: three of them were strongly acidified (pH 4.07–4.57, concentration of reactive aluminium R-Al 448–1913 μg L⁻¹), two were moderately acidified (pH 5.08–6.38, R-Al 52–261 μg L⁻¹) and one non-acidified (pH 7.63–7.89, R-Al 12–59 μg L⁻¹). The largest biotic difference detected by PCA was in the presence of the caddisflies Drusus, Rhyacophila, and Chaetopteryx villosa and stoneflies Leuctra pseudocingulata and Diura bicaudata. The results indicate that at the most acidified sites (the Lysina and the right branch of the Litavka), the process of biological recovery has not started yet due to an insufficient increase in stream pH. Indeed, MAGIC modelling published earlier shows that significant increases cannot be expected in the following decades. An average pH of at least 4.5 is needed for return of less acid-tolerant taxa such as Diura bicaudata, Leuctra major, L. pseudocingulata, L. pseudosignifera, Drusus or Rhyacophila. However, at the Sklářský potok — Jizerka site,^both the clear-cut of mature spruce plantations in 1984–1990 and the regional drop in SO₂ emissions in the 1990s resulted in a decline of acid deposition and rising streamwater pH. Mean annual pH at the Sklářský potok — Jizerka outlet increased from 4.0 (1982–1985) to 5.3 (1990–1994), but episodic acidification has still resulted in a delay in recovery of the biota, particularly acid-sensitive species, which may be expected within a couple decades.